Yield potential and economics of elephant foot yam (Amorphophallus paeoniifolius) + greengram (Vigna radiata) intercropping system as influenced by mulching and fertilizers levels - Nedunchezhiyan, M; Byzu, G; Naskar, S K (The Indian Journal of Agricultural Sciences, 2008)
A field experiment was conducted for 3 years during 2003-04 to 2005-06 in acid laterite soil under rainfed conditions to assess the yield potential and economics of elephant foot yam (Amorphophallus paeoniifolius (Dennst.) Nicolson) + greengram (Vigna radiata L. R. Wilczek) intercropping under varying levels of fertilizer and mulching. Application of 2 tonnes/ha dried farmwaste as mulch increased elephant foot yam yield by 21.6% over the no mulch. However, no effect was found on greengram. Increasing the fertilizer levels beyond N:F:K @ 80:60:80 kg/ha did not increase significantly the elephant foot yam tuber yield, greengram grain yield and tuber equivalent yield. The maximum gross returns (Rs 1 07 575) was obtained with the application of N:P:K @ 120:90:120 kg/ha along with mulching. However, application of N:P:K @ 100:75: 100 kg/ha along with mulching registered higher net returns (Rs 53 785) owing to lesser cost of cultivation. Production efficiency (kg/ha/day) followed similar trends of gross returns and the maximum production efficiency (512.3 kg/ha/day) was found with the application of N:P:K @ 120:90:120 kg/ha along with mulching. The benefit : cost ratio analysis revealed that the maximum benefit : cost ratio was found with the application of N:P:K @ 80:60:80 kg/ha along with mulching (2.02).